PERSEPSI PETANI TERHADAP VARIETAS UNGGUL BARU INPARI 30 DAN 33 DI DESA TANJUNGSARI KECAMATAN BANYUDONO KABUPATEN BOYOLALI - Ningtyas, Denissa Ayu; Suwarto, Suwarto; Wijianto, Arip (Universitas Sebelas Maret, 2018)
This research aimed to analyze the farmers’ perception, to analyze the factors composing the farmers’ perception, to analyze the relationship between factors composing perception and the farmers’ perception on new superior cultivars of Inpari 30 and 33, and to analyze the difference of perception between the farmers using Inpari 30 and 33 new superior cultivars and those not using them. The fundamental research method employed was a descriptive qualitative with survey technique. The research location was determined purposively. The sample was taken using Quota Random Sampling, consisting of 60 respondents. Data analysis was carried out using Spearman’s rank and Mann Whitney’s U analyses. The result of research showed that there was a very significant relationship between non-formal education and farmers’ perception on Inpari 30 and 33 new superior cultivars, at significance level of 99%. Meanwhile, age, formal education, length of time becoming farmers, land width, and land ownership factors were not correlated significantly. There was a difference of perception between the farmers and those using Inpari 30 and 33 new superior cultivars.